2013
DOI: 10.1021/jp4023844
|View full text |Cite
|
Sign up to set email alerts
|

Critical Impact of Gate Dielectric Interfaces on the Contact Resistance of High-Performance Organic Field-Effect Transistors

Abstract: Extensive research on organic field-effect transistors (OFETs) performed to date investigated separately the electronic contact and the gate dielectric interfaces but rarely probed the relation between the two. In this report, the strong impact of the gate dielectric on the contact resistance (R c ) is revealed. With the same semiconductor dioctylbenzothienobenzothiophene (C8-BTBT) and the same device configuration, the R c value varies greatly from 10 to 66 kΩ•cm depending on the gate dielectric interfaces. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
121
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(125 citation statements)
references
References 71 publications
(123 reference statements)
3
121
1
Order By: Relevance
“…Although previous research has focused on charge trapping in the channel region, [ 15,16,[34][35][36][37] trapping events in the injection region are also important. [38][39][40][41] First, we tried to control thickness of P(NDI2OD-T2) layers to examine the role of the semiconductor bulk. The normalized I D decay of the devices with P(NDI2OD-T2) layers of varied thickness was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous research has focused on charge trapping in the channel region, [ 15,16,[34][35][36][37] trapping events in the injection region are also important. [38][39][40][41] First, we tried to control thickness of P(NDI2OD-T2) layers to examine the role of the semiconductor bulk. The normalized I D decay of the devices with P(NDI2OD-T2) layers of varied thickness was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The group of R tot -L linear-regression lines often converge at a common point, called the convergence point (CP), which can be used to qualify the charge injection and charge transport [29]. When there is considerable scatter in m and V th (e.g., OFETs on bare SiO 2 with significant trapping effect), a modified TLM (M-TLM) is suggested to improve extraction accuracy [30,31]. Furthermore, to extract R c in a saturated regime, power TLM (P-TLM) should be applied by measuring the output characteristics (I d -V d ), which are derived from the dissipated power in the whole device regardless of the linear or saturated source-drain electric field [32].…”
Section: Evaluation Of Contact Injection In Ofetsmentioning
confidence: 99%
“…Due to (a) and Eqn 7, it has been observed that R c also exhibits a power dependence on V g [31,49] ðR c À R c0 Þ / jV g À V th j g ;…”
Section: Role Of Transport Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies also show the strong influence of the gate dielectric interface on the contact resistance. 31,32 In summary, the contact resistance in Fe-OFETs was significantly reduced by using an ultrathin PMMA layer inserted between the ferroelectric polymer and organic semiconductor layers. Our investigations revealed that such an enhanced charge injection was due to the narrowing of the trap distribution in the access region of Fe-OFETs after buffering the interfacial polarization fluctuation.…”
mentioning
confidence: 98%